Imaging evaluation of lymphadenopathy and patterns of lymph node spread in head and neck cancer. Issue 2 (February 2014) - Forghani, Reza; Yu, Eugene; Levental, Mark; Som, Peter M; Curtin, Hugh D
<x xml:space="preserve">Abstract</x> Accurate and consistent characterization of metastatic cervical adenopathy is essential for the initial staging, treatment planning and surveillance of head and neck cancer patients. While enlarged superficial nodes may be clinically palpated, imaging allows identification of deeper adenopathy as well as clinically unsuspected pathology and thus imaging has become an integral part of the evaluation of most head and neck cancers patients. This review will focus on the evaluation of cervical adenopathy, summarizing the currently used nomenclature and imaging approach for determining cervical lymph node metastases in head and neck malignancies. The imaging-based classification, which has also been adopted by the American Joint Committee on Cancer, will be presented, the morphologic characteristics used to identify metastatic nodes will be reviewed and the typical nodal spread patterns of the major mucosal cancers of the head and neck will be examined.